Regularidade global Gevrey das soluções de certas classes de operadores parciais lineares de primeira ordem - Coelho, Laurencie Salles (2004)
In this work we study global Gevrey hypoellipticity on the Euclidean 2-space R² for a class of first order linear partial differential operators with coeffcients in Cw2χ (R). Necessary and suffcient conditions for global Gevrey hypoellipticity are proposed.